Effects of Mucuna pruriens on Free Fatty Acid Levels and Histopathological Changes in the Brains of Rats Fed a High Fructose Diet - Akgun, Bekir; Sari, Aysel; Ozturk, Sait; Erol, Fatih Serhat; Ozercan, Ibrahim Hanifi; Ulu, Ramazan (Karger, 2017)
Objective: To investigate free fatty acid levels and histopathological changes in the brain of rats fed a high fructose diet (HFrD) and to evaluate the effects of Mucuna pruriens, known to have antidiabetic activity, on these changes. Materials and Methods: The study comprised 28 mature female Wistar rats. The rats were divided into 4 groups, each included 7 rats. Group 1: control; group 2: fed an HFrD; group 3: fed normal rat chow and M. pruriens; group 4: fed an HFrD and M. pruriens for 6 weeks. At the end of 6 weeks, the rats were decapitated, blood and brain tissues were obtained. Serum glucose and triglyceride levels were measured. Free fatty acid levels were measured in 1 cerebral hemisphere of each rat and histopathological changes in the other. The Mann-Whitney U test was used to compare quantitative continuous data between 2 independent groups, and the Kruskal-Wallis test was used to compare quantitative continuous data between more than 2 independent groups. Results: Arachidonic acid and docosahexaenoic acid levels were significantly higher in group 2 than in group 1 (p < 0.05). Free arachidonic acid and docosahexaenoic acid levels in group 4 were significantly less than in group 2 (p < 0.05). Histopathological examination of group 2 revealed extensive gliosis, neuronal hydropic degeneration, and edema. In group 4, gliosis was much lighter than in group 2, and edema was not observed. Neuronal structures in group 4 were similar to those in group 1. Conclusions: The HFrD increased the levels of free arachidonic acid and docosahexaenoic acid probably due to membrane degradation resulting from possible oxidative stress and inflammation in the brain. The HFrD also caused extensive gliosis, neuronal hydropic degeneration, and edema. Hence, M. pruriens could have therapeutic effects on free fatty acid metabolism and local inflammatory responses in the brains of rats fed an HFrD. (C) 2017 The Author(s) Published by S. Karger AG, Basel
Keywords: Brain; Free fatty acids; Fructose; Histopathology; Mucuna pruriens